Pokémon adventures : heart gold & soul silver. Volume 02 - Kusaka, Hidenori (Pokémon adventures, 2013)
Crystal and Gold battle the enemy while Silver collects the sixteen mysterious plates that Team Rocket wants to get their hands on to set their latest diabolical plan in motion.